2D Metal Zn Nanostructure Electrodes for High‐Performance Zn Ion Supercapacitors. Issue 3 (29th November 2019) - An, Geon‐Hyoung; Hong, John; Pak, Sangyeon; Cho, Yuljae; Lee, Sanghyo; Hou, Bo; Cha, SeungNam
Abstract: Recent supercapacitors show a high power density with long‐term cycle life time in energy‐powering applications. A supercapacitor based on a single metal electrode accompanying multivalent cations, multiple charging/discharging kinetics, and high electrical conductivity is a promising energy‐storing system that replaces conventionally used oxide and sulfide materials. Here, a hierarchically nanostructured 2D‐Zn metal electrode‐ion supercapacitor (ZIC) is reported which significantly enhances the ion diffusion ability and overall energy storage performance. Those nanostructures can also be successfully plated on various flat‐type and fiber‐type current collectors by a controlled electroplating method. The ZIC exhibits excellent pseudocapacitive performance with a high energy density of 208 W h kg −1 and a power density from 500 W kg −1, which are significantly higher than those of previously reported supercapacitors with oxide and sulfide materials. Furthermore, the fiber‐type ZIC also shows high energy‐storing performance, outstanding mechanical flexibility, and waterproof characteristics, without any significant capacitance degradation during bending tests. These results highlight the promising possibility of nanostructured 2D Zn metal electrodes with the controlled electroplating method for future energy storage applications. Abstract : 2D‐Zn electrodes are fabricated using a stepwise electroplating process on flat and flexible metal substrates. Their hierarchical structure and interconnected morphology can provide an excellent capacitance, rate retention, and cycling stability due to the enlarged surface area and the shortened diffusion paths, which are promising for use in future energy storage systems.